PROFIL INDUSTRI BULU MATA DAN RAMBUT PALSU DI KABUPATEN PURBALINGGA - Virea Stacia; Edy Yusuf Agung Gunanto (Diponegoro Journal of Economics, 2014)
ABSTRACTThe objective of this research was perceiving fake hair and eyelashes industry’s growth in Purbalingga. It was one of the biggest fake hair and eyelashes industry in Indonesia, even in Asia which its distribution reached out a lot of countries.This research used qualitative descriptive method by collecting data which used purposive sampling then it used interviewmethod to entrepreneurs and consumers. It also used observation method to those industries.The result of this research showed that fake hair and eyelashes industry became the economy supporter in Purbalingga. Supporting factor of this industry was a very good bussiness condition in Purbalingga. The local government also supported by entering foreign investors who want to invest. Nevertheless, there are some constraints for this industry’s growth, such as coordination problem that occured with local government, especially Dinas Perindustrian Perdagangan dan Koperasi. They were less able to collaborate with local government about reporting of production data because they were afraid with taxation. There were also other problems occured in society that triggered by lifestyle.